The spirit and the body: towards a womanist pentecostal social justice ethic - Stone, Selina R. (Global religion, 2023)
This book represents the first womanist analysis of pentecostal theology, spirituality and ministry in relation to social inequity and oppression in the West. Despite its designation as an 'embodied faith', this book argues that both historically and in the present, classical pentecostalism often fails to integrate the body with spirituality in ways which attend to the hierarchies which oppress certain bodies in the church and the wider world. Looking back to the African and Wesleyan roots of the movement to explore this tension, the book then draws on qualitative as well as textual research, to analyse classical progressive pentecostalism in Britain today which models an integrated pentecostal faith to an extent, but retains inconsistencies. Finally, a womanist pentecostal theology is being constructed, which calls attention to the Spirit and the body - especially the bodies of the oppressed - as a path towards a holistic understanding of the work of the Spirit and pentecostal faith and ministry